Affective instability, childhood trauma and major affective disorders. - Marwaha, S; Gordon-Smith, K; Broome, M; Briley, P; Perry, A; Forty, L; Craddock, N; Jones, I; Jones, L (Elsevier, 2015)
Affective instability (AI), childhood trauma, and mental illness are linked, but evidence in affective disorders is limited, despite both AI and childhood trauma being associated with poorer outcomes. Aims were to compare AI levels in bipolar disorder I (BPI) and II (BPII), and major depressive disorder recurrent (MDDR), and to examine the association of AI and childhood trauma within each diagnostic group.AI, measured using the Affective Lability Scale (ALS), was compared between people with DSM-IV BPI (n=923), BPII (n=363) and MDDR (n=207) accounting for confounders and current mood. Regression modelling was used to examine the association between AI and childhood traumas in each diagnostic group.ALS scores in descending order were BPII, BPI, MDDR, and differences between groups were significant (p<0.05). Within the BPI group any childhood abuse (p=0.021), childhood physical abuse (p=0.003) and the death of a close friend in childhood (p=0.002) were significantly associated with higher ALS score but no association was found between childhood trauma and AI in BPII and MDDR.The ALS is a self-report scale and is subject to retrospective recall bias.AI is an important dimension in bipolar disorder independent of current mood state. There is a strong link between childhood traumatic events and AI levels in BPI and this may be one way in which exposure and disorder are linked. Clinical interventions targeting AI in people who have suffered significant childhood trauma could potentially change the clinical course of bipolar disorder.